Pengaruh Motivasi Kerja, Pelatihan, Kompetensi, dan Kepuasan Kerja terhadap Prestasi Kerja Pegawai Dindikbud Kabupaten Purbalingga - Ari Fatah Asrofi; Heri Setiawan; Ady Achadi (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
This research is based on the gap phenomenon in the form of the level of work achievement of employees which is considered not optimal. Condition can demonstrated through reports on the work achievements of Purbalingga Regency Education and Culture Service employees and research gaps in the form of differences in research results for each variable. The aim of this research is to analyze the influence of work motivation, training, competence and job satisfaction on the work performance of employees of the Purbalingga Regency Education and Culture Service. The population in this study ASN employees of the Purbalingga Regency Education and Culture Service, totaling 86 people with a sample of 75 respondents. The data analysis method used is multiple linear regression and hypothesis testing using t test calculations. The results of this research show work motivation, training, competence and job satisfaction influence work performance. From the results the research, can be implied that the leadership of the Purbalingga Regency Education and Culture Office needs to provide recognition to employees, needs to pay more attention to the qualifications of trainers for employees, increases responsiveness in carrying out work, needs to pay attention to the amount of payment an employee receives as needed.